2020
DOI: 10.3390/atmos11030303
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations of Precipitation in China Using Surface Gauge Observations from 1961 to 2016

Abstract: Long-term precipitation trend is a good indicator of climate and hydrological change. The data from 635 ground stations are used to quantify the temporal trends of precipitation with different intensity in China from 1961 to 2016. These sites are roughly uniformly distributed in the east or west regions of China, while fewer sites exist in the western region. The result shows that precipitation with a rate of <10 mm/day dominates in China, with a fraction of >70%. With a 95% confidence level, there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…The summer RA trend was very similar to the annual trend; the RA in eastern China generally decreased in autumn; and the winter RA in the northern part of eastern China decreased significantly, while increasing in the south. Many researchers have confirmed that the annual RA in Northwest China has exhibited an obviously increasing trend [35,36,[55][56][57]. The fact that the RA has increased in winter and summer but decreased in spring and autumn has been recognized by most researchers [55,58,59].…”
Section: Comparison Of These Research Results With Those Of Other Stumentioning
confidence: 98%
“…The summer RA trend was very similar to the annual trend; the RA in eastern China generally decreased in autumn; and the winter RA in the northern part of eastern China decreased significantly, while increasing in the south. Many researchers have confirmed that the annual RA in Northwest China has exhibited an obviously increasing trend [35,36,[55][56][57]. The fact that the RA has increased in winter and summer but decreased in spring and autumn has been recognized by most researchers [55,58,59].…”
Section: Comparison Of These Research Results With Those Of Other Stumentioning
confidence: 98%
“…It is an essential input for hydrological modelling and also forms the basis of hydrological, agricultural research applications, environment studies, and climate change studies [1,2]. It is seen that areas of high rain gauge density give more reliable precipitation estimates than those of low-density areas [3,4]. However, due to economic constraints and infeasible natural conditions, such as in the Arctic [5] and in the Tibetan Plateau, ground-based observations are usually sparse, especially in several developing countries, where ground-based rainfall observation networks have always been relatively sparse [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is a fundamental part of the hydrological cycle, which is of great significance in meteorology, hydrology, ecology and other scientific research areas [1,2]. Precipitation is a complex natural phenomenon which is characterized by a significant variability both in time and space [3][4][5]. Therefore, accurate precipitation data are extremely important for water resource-related research.…”
Section: Introductionmentioning
confidence: 99%